Tik Tok Popularism and Nationalism: Rethinking National Identities and Boundaries on Millennial Popular Cultures in Indonesian Context - Budi Kurniawan (Proceedings of AICS - Social Sciences, 2018)
One of creative video application android that is popular today in Indonesia is Tik Tok. Tik Tok became one of medium to express the creativity of art in cyberspace. With the popularity of this application that has been downloaded more than 50 million android user in the world, this application creates complex implications for the culture of popular millennial globally, especially in Indonesia. The millennial generation of Indonesia is presented by the global cultural industries. It can be found in various forms of popular culture that better reflect western culture so as to make local self-reliance pessimism on the part of communities in Indonesia. This application indirectly is a medium that used to establish exploitation of the taste and as an instrument in the construction of popular culture that existed in Indonesia. It should be noted in this context is the process of westernization. In the context of globalization, westernization has been examined. But things need to be examined again is how the value of local and National Identity in the popular culture of millennial Indonesia experienced marginalization. By using the perspective of critical and cultural sociology, this paper critiquing the Tik Tok phenomena became one of popular culture's trendsetter in the millennial era of Indonesia at the moment. Popular culture is supposed to be very productive in instilling national values. If not handled properly, most of the younger generation of Indonesia could well lose the identity as well as his nationalist pride.Keywords: Tik Tok, nationalism, identity.